Effect of Sowing Patterns and Nitrogen Rates on Quality Traits and Yield of Wheat (Journal of Environmental Science and Natural Resources, 2012)
The experiment was conducted to study the effect of sowing patterns and N rates on quality traits and yield of wheat. The experiment consisted of two methods of sowing viz.; conventional sowing (S1) and bed sowing (S2) and four wheat varieties namely; Protiva (V1), Sourav (V2), Shatabdi (V3) and Prodip (V4) and four levels of nitrogen viz; 0 (N1), 60 (N2), 110 (N3) and 160 (N4) kg N ha-1. Grain yield was higher in bed planting system than conventional one due to improvement in yield components. Grain yield was increased with increasing rates of nitrogen application. Prodip produced the highest grain yield with 160 Kg N ha-1. The highest grain yield was found with the combination of bed sowing method and 160 Kg N ha-1 and the lowest one was recorded with the combination of conventional method at control treatment. Nitrogen and Protein content in grain and straw varied significantly due to method of sowing. The highest nitrogen and protein content in grain and straw were recorded in bed planting system. Nitrogen content of grain was highest at 160 Kg N ha-1.The overall results indicate that among the varieties Prodip showed better performance in bed planting system. Prodip gave maximum grain yield at 160 Kg N ha-1 in bed planting system. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11591 J. Environ. Sci. & Natural Resources, 5(1): 267-272, 2012